I have found a curve fit for some experiments that I have done and got the equation.

Y = (A x ( Flow^B))+ (C x (Flow^D))

Can anyone help in transposing the formulae to give Flow=, I cant remember maths to this level although I can still transpose trig and other simpler equations.

Steve Larner

Y = (A x ( Flow^B))+ (C x (Flow^D))

Can anyone help in transposing the formulae to give Flow=, I cant remember maths to this level although I can still transpose trig and other simpler equations.

Steve Larner

## Comment